2001
DOI: 10.1128/jvi.75.8.4019-4022.2001
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Nucleotides in the Infectious, Pathogenic Simian Immunodeficiency Virus Clone SIVmac239

Abstract: We analyzed virus sequences in two monkeys infected with SIVmac239 and two monkeys infected with SHIVnef that maintained high, persisting viral loads. Sequence changes were observed consistently at four loci in all four animals: a single nucleotide change in the Lys-tRNA primer binding site in the 5 long terminal repeat; two nucleotide changes that resulted in two amino acid changes in the pol gene product; and a single nucleotide change in the region of the simian immunodeficiency virus genome where the rev a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 26 publications
5
39
0
Order By: Relevance
“…In fact, all the clones replicated more robustly than SIVmac239 as long as the cells were derived from a TRIM5␣-permissive donor. This may be due to the suboptimal nucleotides still present in the parental SIVmac239 (35,37). Consistent with this idea, we recently reported that correcting these suboptimal changes increased in vitro replication (37).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In fact, all the clones replicated more robustly than SIVmac239 as long as the cells were derived from a TRIM5␣-permissive donor. This may be due to the suboptimal nucleotides still present in the parental SIVmac239 (35,37). Consistent with this idea, we recently reported that correcting these suboptimal changes increased in vitro replication (37).…”
Section: Discussionsupporting
confidence: 72%
“…SIVmac239 was originally derived by lambda phage cloning from DNA isolated following coculture of macaque plasma obtained during late-stage simian AIDS with the human cell line HUT-78 (32). The original SIVmac239 clone contained a premature stop codon in the nef gene and at least four additional suboptimal nucleotides (33)(34)(35). The nef mutation was subsequently corrected through site-directed mutagenesis prior to widespread use (36), but a clone with the 4 additional suboptimal mutations corrected has only recently been made available (37).…”
mentioning
confidence: 99%
“…We found that a mutation leading to an arginine (R)-to-glycine (G) alteration at the 751st aa in Env and a lysine (K)-to-R alteration at the 40th aa in Rev was dominant at week 5 in both of them. The wild-type sequence at this position in the SIVmac239 molecular clone is considered to be a suboptimal nucleotide that frequently reverts to an alternative sequence in vivo (2,31). Indeed, we found this mutation also in the noncontrollers, indicating no association of this mutation with viral control or evasion in the present study.…”
Section: Discussionmentioning
confidence: 29%
“…Asterisks indicate the residues where different mutations were detected. It is known that amino acid substitutions at the Pol residues 413 and 821 and the Rev residue 40 are frequently observed in SIVmac239 infection and contribute to higher viral fitness in vivo (1,39). differences in plasma viral loads, peripheral CD4 ϩ T-cell counts, survival periods, Gag-specific CD8 ϩ T-cell responses, and numbers of viral gag mutations.…”
Section: Figmentioning
confidence: 99%